ROLE OF PHYSICAL MEDICINE AND REHABILITATION INTERVENTION FOR PLANTAR FASCIITIS: Rehabilitation Intervention for Plantar Fasciitis - Akhtar, Noreen; Rasheed, Pervaiz; Ahmad, Zaheer (Pakistan Armed Forces Medical Journal, 2008)
Objective: To highlight the role of early physical medicine and rehabilitation. Design: Randomized case control study. Place and Duration of Study: Armed Forces Institute of Rehabilitation Medicine Rawalpindi from March 2002 to March 2003. Patients and Methods: Eighty patients of both sexes between 25-45 years of age were randomly divided into Study and Control group. Group 1 (study) was given standard physiatric therapeutic intervention and Group 2 (control) was given conventional treatment with heel cup and Non Steroid anti inflammatory drugs (NSAIDs). They were followed up for three months. Pain was assessed by Visual Analog Scale (VAS) and Heel Tenderness Index (HTI). Results: Mean age of the patients was 35.7 years. Forty percentage cases were male and 60 % were female. After three months of treatment, 75% of group 1 and 20% of group 2 showed marked improvement (VAS < 30mm). On HTI index, 72.5% of patients were in Grade 0 (no pain) and 22.5% were in Grade I while 30% of patients in group 2 were in grade 1 (painful). Difference was found to be statistically significant i.e. P- value < 0.05. Conclusion: Comprehensive rehabilitation management has shown promising results in the treatment of plantar fasciitis especially when initiated in early stages and may prove to be the mainstay modality in the treatment of plantar fasciitis in future.